Realization of efficient field emitter based on reduced graphene oxide-Bi2S3 heterostructures - Gote, Gorkshnath H.; Bhopale, Somnath R.; More, Mahendra A.; Late, Dattatray J. (Physica Status Solidi A-Applications and Materials Science, 2019)
Herein, Bi2S3 nanorods and reduced graphene oxide (rGO)-Bi2S3 heterostructures are synthesized using a simple hydrothermal method. The structural, morphological, chemical, and elemental analysis of as-synthesized materials is performed using X-ray diffraction (XRD), Raman spectroscopy, field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Field emission (FE) studies are carried out on both pristine Bi2S3 nanorods and rGO-Bi2S3 heterostructure samples at a base pressure of approximate to 1 x 10(-8) mbar. The results show that the rGO-Bi2S3 heterostructure emitter has superior FE performance compared to pristine Bi2S3 emitters in terms of the turn-on field (2.6 V mu m(-1) at 10 mu A cm(-2)) and threshold field (4.0 V mu m(-1) at 100 mu A cm(-2)) along with a high emission current density of approximate to 1464 mu A cm(-2) at an applied electric field of 7.0 V mu m(-1). The rGO-Bi2S3 heterostructure emitter exhibits very good emission current stability, tested for more than 3 h duration, characterized by standard deviation values approximate to 2.84 and 4.06, corresponding to preset values 12 and 100 mu A. This study implies that one-step hydrothermal route can be efficiently used to synthesize organic-inorganic heterostructures that possess unique morphology. Furthermore, the synthesized rGO-Bi2S3 heterostructure emitter shows potential as an electron source for practical application in vacuum microelectronic devices.
Keywords: Bi2S3; field emission; Heterostructures; Nanorods; Reduced graphene oxide